The Degree of Employment of Social Studies Teachers in Public Schools in the State of Kuwait of Productive Thinking Skills from their Point of View - Al-Ajmi, Mubarak Falah Hamid; Al-Ajmi, Muhammad Ali Rashid (Dirasat: Educational Sciences, 2023)
Objectives: The study aims to identify to what extent social studies teachers in public schools in Kuwait employ productive thinking skills in their lessons. Similarly, the study investigates whether there are statistically significant differences in the degree of practice in terms of gender and educational qualification. Methods: To answer the questions of the study, a questionnaire of 24 paragraphs was conducted using the descriptive quantitative research approach. A random stratified sampling method was used to select a sample of (298) teachers of social studies in government schools in the Al-Ahmadi educational district in the State of Kuwait Results: Specifically, the study revealed that social studies teachers employed productive thinking skills to a high degree from their perspective, with a total arithmetic average of the resolution paragraphs (3.86) and a standard deviation (0.81) in Kuwait's public schools. The findings also revealed that there were no statistically significant differences in the degree of practice in terms of gender and educational qualification. Conclusions: Even though social studies teachers in Kuwait possess a high degree of productive thinking skills, the study recommended continuing to provide quality training programs to help them employ these skills in a more effective teaching and learning environment.